A morphometric system to distinguish sheep and goat postcranial bones - Salvagno, Lenny; Albarella, Umberto (PLOS ONE, 2017)
Distinguishing between the bones of sheep and goat is a notorious challenge in zooarchaeology. Several methodological contributions have been published at different times and by various people to facilitate this task, largely relying on a macro-morphological approach. This is now routinely adopted by zooarchaeologists but, although it certainly has its value, has also been shown to have limitations. Morphological discriminant criteria can vary in different populations and correct identification is highly dependent upon a researcher’s experience, availability of appropriate reference collections, and many other factors that are difficult to quantify. There is therefore a need to establish a more objective system, susceptible to scrutiny. In order to fulfil such a requirement, this paper offers a comprehensive morphometric method for the identification of sheep and goat postcranial bones, using a sample of more than 150 modern skeletons as a basis, and building on previous pioneering work. The proposed method is based on measurements—some newly created, others previously published–and its use is recommended in combination with the more traditional morphological approach. Measurement ratios, used to translate morphological traits into biometrical attributes, are demonstrated to have substantial diagnostic potential, with the vast majority of specimens correctly assigned to species. The efficacy of the new method is also tested with Discriminant Analysis, which provides a successful verification of the biometrical indices, a statistical means to select the most promising measurements, and an additional line of analysis to be used in conjunction with the others.